PENGARUH KEPEMILIKAN INSTITUSIONAL, KOMISARIS INDEPENDEN DAN KOMITE AUDIT TERHADAP PENGHINDARAN PAJAK - Risa Aulia Rana; Dudi Pratomo (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2021)
The purpose of this study is to determine whether there is an influence of institutional ownership, independent commissioners and audit committees on tax avoidance of consumer goods companies listed on the Indonesia Stock Exchange for the period 2015-2018. This research uses quantitative descriptive. The sampling technique used was purposive sampling with a total sample of 14 companies within 4 years so that 56 samples were obtained after data outliers were carried out. The analysis used is panel data analysis using Eviews 10. The analysis test results state that institutional ownership variables, independent commissioners, and audit committees have an influence on simultaneous tax avoidance. Partial testing stated that the variable of institutional ownership and independent commissioners had a negative effect on tax avoidance, while the audit committee had no effect on tax avoidance.